The rediscovery and redescription of Epigomphus pechumani Belle, 1970 (Odonata: Gomphidae), with a description of its female from the Western Colombian Andes - Bota-Sierra, Cornelio A.; Novelo-Gutiérrez, Rodolfo; Amaya-Vallejo, Vanessa (Zootaxa, 2017)
Epigomphus pechumani Belle, 1970, was described based upon a single male specimen in poor condition, lacking specific locality in Colombia. Here the male is redescribed and the female is described and illustrated for the first time based on a total of 18 adults collected in Tatamá National Park, Risaralda Department, and Farallones de Cali National Park, Valle del Cauca Department, Colombia. A diagnosis, notes on its biology and a distributional map are presented. All material is deposited in the Entomological collection of Universidad de Antioquia.